The impact of new entrants and the new entrant program on motor carrier safety performance. (January 2017) - Cantor, David E.; Corsi, Thomas M.; Grimm, Curtis M.
Highlights: The FMCSA requires motor carriers to participate in the new entrance safety program. This study examines the relationship of the new entrant program to safety performance. More experienced carriers have better safety performance than new entrant carriers. New entrants who successfully complete the program are safer than those who fail it. Abstract: Due to the importance of the recent Federal Motor Carrier Safety Administration requirement that all motor carriers participate in the New Entrant Safety Assurance Program (NESAP), the purpose of this study is to examine the relationship of the NESAP to motor carrier safety performance. Our study finds that carriers who entered the industry before the NESAP program (e.g., more experienced carriers) have significantly better safety performance in comparison to new entrant carriers. We also demonstrate that new entrants who successfully complete the requirements of the NESAP have significantly better safety performance than new entrants who fail to complete the program successfully. The implications of the study are also discussed.